MENYELAMI TAFSIR AYAT AHKĀM RAWĀ’I AL-BAYĀN FI TAFSĪR ĀYĀT AL-AHKĀM KARYA SYEKH ‘ALI AL-SHĀBUNĪ - Ratoni (Al Naqdu, 2025)
This study aims to dissect the Book of Rawā’i al-Bayān fi Tafsīr āyāt al-Ahkām by Sheikh ‘Ali al-Shābunī. Specifically, this study explains a) Biography of the Author of the Book “Rawāi’u al-Bayān” Sheikh ‘Ali al-Shabunī b) Method and style of interpretation of “Rawāi’u al-Bayān, c) 10 steps in exploring the content of legal verses in the Tafsir “Rawāi’u al-Bayān. This study uses a qualitative approach with library research techniques. The method used is content analysis technique. The results of this study indicate that this interpretation is quite unique because it combines 4 methods at once, namely: the tahlilī method (analysis), ijmālī (global meaning), muqâran (comparison) and maudhū’ī (thematic), although the tahlilī method is more dominant. Another uniqueness is that this interpretation uses a ten-step approach in explaining each theme of the verse, making this interpretation more interesting. By carrying out the interpretation of legal verses, al-Shābunī focuses more on the discussion of the legal aspect. Of the ten steps in explaining each theme of the verse, the study of legal content dominates the discussion.